2001
DOI: 10.1074/jbc.m009404200
|View full text |Cite
|
Sign up to set email alerts
|

Core LXXLL Motif Sequences in CREB-binding Protein, SRC1, and RIP140 Define Affinity and Selectivity for Steroid and Retinoid Receptors

Abstract: An ␣-helical motif containing the sequence LXXLL is required for the ligand-dependent binding of transcriptional co-activators to nuclear receptors. By using a peptide inhibition assay, we have defined the minimal "core" LXXLL motif as an 8-amino acid sequence spanning positions ؊2 to ؉6 relative to the primary conserved leucine residue. In yeast two-hybrid assays, core LXXLL motif sequences derived from steroid receptor co-activator (SRC1), the 140-kDa receptor interacting protein (RIP140), and CREB-binding p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
99
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 145 publications
(106 citation statements)
references
References 50 publications
6
99
0
1
Order By: Relevance
“…For example, TIP60 has been reported to bind the Class I receptors, but displayed little interaction with VDR, TR, or RXR (22). The p160s interact with a wide range of NRs, although individual LXXLL motifs derived from these proteins display differential binding to NRs (14,38). In addition, we have shown that LXXLL sequences derived from CBP and RIP140 show selectivity that is at least partly determined by the LXXLL core sequences (14).…”
mentioning
confidence: 84%
See 4 more Smart Citations
“…For example, TIP60 has been reported to bind the Class I receptors, but displayed little interaction with VDR, TR, or RXR (22). The p160s interact with a wide range of NRs, although individual LXXLL motifs derived from these proteins display differential binding to NRs (14,38). In addition, we have shown that LXXLL sequences derived from CBP and RIP140 show selectivity that is at least partly determined by the LXXLL core sequences (14).…”
mentioning
confidence: 84%
“…The constructs AAD-AR-LBD-(625-919), AAD-PR-LBD-(633-933) (44), AAD-ER␣-LBD-(282-595) (4), AAD-RAR␣-LBD-(200 -462), and AAD-RXR␣-LBD-(230 -467) (14) have been described previously. The constructs AAD-PPAR␥-LBD-(173-475) and AAD-TR␤-(1-456) were generated by cloning PCR fragments into the modified pASV3.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations